Financial reconstruction in conflict and post-conflict economies - Tony Addison; Alemayehu Geda; Philippe Le Billon; S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper discusses some of the principal issues relating to the reconstruction of the financial sector in conflict-affected countries, focusing on currency reform, the rebuilding (or creation) of central banks, the revitalization of the banking system, and its prudential supervision and regulation. Different types of conflict have different effects on the financial system. Country priorities for reconstruction therefore vary accordingly. Nevertheless, the following problems repeatedly occur in reconstruction. First, central banks often remain weak and under-resourced. The consequence is haphazard and lenient supervision of the financial system, which is compounded by the frequently lax accounting and reporting standards of commercial banks. This hinders the application of international models of prudential supervision, such as the Basle Core Principles. Second, regulatory forbearance is common, reflecting both the technical weakness of central banks, but also the pressure of powerful interests—including war criminals—that straddle both state institutions and the financial sector. The consequences are leniency in the licensing of banks, insider-lending, excessive risk exposure, and a general failure to curb emergent bank crises. These in turn destabilize economies in recovery from war, and the fiscal burden of bank crises limits development and poverty spending—thereby threatening `postconflict' reconstruction itself. – aid ; conflict ; financial development ; sub-Saharan Africa
Keywords: O10; O55; 330; Währungsreform; Zentralbank; Bankensystem; Bankenpolitik; Zentralafrika; Politischer Konflikt